REGULATORY DUALISM AND POLYCENTRIC GOVERNANCE IN MTs: CHALLENGES IN SYNCHRONIZING POLICIES BETWEEN KEMENAG AND KEMENDIKBUDRISTEK - Sri Hayati; Reza Fatchurahman; Musdalifah; Anastasia Hiyang l; Laili Komariyah; Lambang Subaino (SOSIOEDUKASI, 2026)
Regulatory duality in the governance of Madrasah Tsanawiyah (MTs) is a strategic issue in the Indonesian education system, as it involves two policy authorities with differing institutional orientations: the Ministry of Religious Affairs and the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). This situation gives rise to a polycentric governance pattern characterized by multi-actor, multi-regulatory, and multi-level governance in madrasah education management. This article aims to critically analyze the problem of regulatory duality, the dynamics of MTs polycentric governance, and the challenges of synchronizing national and religious education policies within the context of 21st-century educational transformation. Employing a conceptual paper approach based on a systematic literature review of reputable international and national journal articles (2020–2026), educational policy documents, and literature on governance, educational policy, and Islamic education management, this study utilizes critical policy analysis and inter-literature dialogue. The analysis identifies points of regulatory tension, authority fragmentation, and opportunities for reconstructing a more integrative madrasah governance model. The findings indicate that regulatory duality causes policy implementation asynchrony in curriculum, assessment, teacher management, education digitalization, data governance, and institutional accountability mechanisms. Consequently, MTs occupy an ambivalent position between the demands of national educational standardization and the strengthening of Islamic educational identity, generating administrative burdens, policy interpretation conflicts, and governance capacity disparities. The study reveals that hierarchical bureaucratic approaches are no longer adequate to address the complexities of contemporary madrasah education governance. Therefore, a collaborative polycentric governance model is required, positioning regulatory synchronization, data system integration, adaptive leadership, and multi-stakeholder participation as the primary foundation for MTs governance reform. The primary contribution of this article lies in developing a conceptual framework for polycentric madrasah education governance based on cross-ministerial policy integration. This study expands the discourse on Islamic education governance in Indonesia by integrating institutional theory, network governance, and the political economy of education to explain madrasah policy dynamics. The implications emphasize the necessity of reforming the national education regulatory architecture so that madrasahs are no longer positioned as peripheral administrative entities, but as an integral part of an adaptive, inclusive, and sustainable public education system.